2020
DOI: 10.1097/mbp.0000000000000502
|View full text |Cite
|
Sign up to set email alerts
|

Relation between nocturnal decline in blood pressure and choroidal thickness: a comparative analysis in dipper vs. non-dipper hypertensive patients

Abstract: Purpose To compare choroidal thickness (ChT) and echocardiographical changes in patients with dipper and non-dipper systemic arterial hypertension (HT). Methods Patients with HT were evaluated in two groups according to the 24-hour ambulatory BP monitoring. Compared to day-time values, those whose night-time SBP decreased ≥10% were defined as dippers, and those whose SBP decreased <10% were defined as non-dippers. Transthoracic echocardiography was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…However, previous studies mainly focused on ChT in cardiovascular diseases or eye disorders 17,18 . Tas et al 10 reported that ChT in subfoveal and temporal locations were lower in the nondipper group, and they also found a negative correlation between night-time SBP and ChT. They focused on hypertensive patients with/without dipping patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies mainly focused on ChT in cardiovascular diseases or eye disorders 17,18 . Tas et al 10 reported that ChT in subfoveal and temporal locations were lower in the nondipper group, and they also found a negative correlation between night-time SBP and ChT. They focused on hypertensive patients with/without dipping patterns.…”
Section: Discussionmentioning
confidence: 99%
“…ChT in hypertensive patients with nondipper and dipper patterns and found significant differences among these patients 10 . As early identification of vascular changes in normotensive patients with nondipper status may have an impact on the prognosis of such patients, this study aimed to compare ChT and CVI changes in normotensive dippers and nondippers.…”
Section: Choroidal Vascular Changes In Dippers and Nondippersmentioning
confidence: 91%